Examination of the apelin signaling pathway in acetaminophen-induced hepatotoxicity in rats - Dolanbay Turgut; Makav Mustafa; Gul Huseyin Fatih; Karakurt Emin; Bektasoglu Fikret (Türk Biyokimya Dergisi)
The present study identifies the level changes of markers (Apelin, Elabela, Meteorin, ALT, AST, GGT) in the liver after acute intake of high-dose paracetamol and their role in determining liver damage.